PENENTUAN RUANG DAN WAKTU PENANGKAPAN IKAN NELAYAN SUKU BAJO SEBAGAI BENTUK KEARIFAN LOKAL DI DESA WAIWURING KECAMATAN WITIHAMA KABUPATEN FLORES TIMUR - sabon, maria agustina reong; Samin, Mikael; Hasan, Muhammad Husain (Universitas Nusa Cendana, 2024)
Waiwuring Village is one of the villages in the Witihama District. This village is an acculturation of the native population with immigrants from outside East Flores who have long been known as the Bajo Tribe. This research aims to: (1) Find out the ability of Bajo Tribe Fishermen in determining fishing location points. (2) Knowing how Bajo fishermen determine fishing time. (3) Know the methods or strategies of Bajo Tribal Fishermen in catching fish. This type of research is descriptive qualitative. Qualitative descriptive data analysis techniques. The research results are as follows: (1) Bajo fishermen in Waiwuring Village are known as nomadic sea fishermen, who have extensive knowledge about the marine environment and fish movement patterns. The method used to determine fishing locations still relies on the experience and knowledge that is owned and passed down from generation to generation. (2) To determine fishing time, Bajo fishermen have different times depending on what type of fish the Bajo fishermen catch by looking at sea current patterns and natural signs such as the presence of sea birds. (3) Strategies for catching fish so as not to catch fish. conflict occurs, the Bajo Tribe fishermen have developed a traditional success system which is respected by all the Bajo Tribe fishing community in Waiwuring village. It is hoped that we will maintain our abilities in determining the time and place of fishing and it is hoped that fellow fishermen will always share so that these local skills/knowledge can be learned and preserved for future generations.